How to Increase Motivation for Physical Activity among Youth - Izedin Mehmeti; Besim Halilaj (Sport Mont, 2018)
The primary aim of the present study was to explore motivational profi les for physical activity (PA) in current students of secondary schools. The participants of the study were (N=526; males=267 and females=259), 8th grade, and 9th grade students from the four secondary schools in the central and northern part of Kosovo. Data were collected through focus group discussions for students, during the month of May and June 2014/2015 school year, in order to gather qualitative data regarding students’ perceptions of motivation and participation in Physical Education (PE) and extracurricular PA activities. Based on study fi ndings Kosovo schools are not creating supportive and attractive school environment for children and adolescents in doing (PA) and sports in daily basis. Many schools (PE Teachers) make a mistake requiring every child to became an athlete, by suppressing child motivation and enjoyment for sport and creative physical activities. PE and sports module school based should off er the opportunities for diff erent physical activities that people can do for a life time. PE and sports curricula should be focused on giving the opportunity to every child to excel their own skill level, and integrate teaching strategies for “maximum movement for maximum kids”.